Evaluation of antitumor effect of oxygen nanobubble water on breast cancer‐bearing BALB/c mice. Issue 9 (3rd May 2019) - Mahjour, Azita; Khazaei, Majid; Nourmohammadi, Esmail; Khoshdel‐Sarkarizi, Hoda; Ebrahimzadeh‐Bideskan, Alireza; Rahimi, Hamid Reza; Safipour Afshar, Akbar
Abstract: Hypoxia is a condition of low oxygen level which poses a common feature of most cancers. In the current study, we investigated effect of water containing oxygen nanobubble (ONB) on tumor growth in breast cancer 4T1‐bearing mice during 14‐day treatment period. Tumor‐bearing mice were randomly divided into three groups (six mice per group), including the ONB group drinking water containing ONB, the air nanobubble (ANB) group drinking water containing ANB, and control group drinking normal water. Tumor weight and size were measured in 2‐day interval during 14‐day treatment. mRNA expression of p53, vascular endothelial growth factor (VEGF), hypoxia‐inducible factor (HIF), and cyclin D/Cdk2 genes were measured in the treated and control mice. After 8, 12, and 14 days of treatment, tumor size in ONB group was significantly decreased by 40.5%, 32.8%, and 28%, respectively, when compared with the control group. In addition, ANB group showed a significant reduction in tumor burden as well. The messenger RNA (mRNA) level of p53 in tumor cells of ONB and ANB group was found to be 36‐fold ( P  = 0.0001) and 33‐fold ( P  = 0.0001) higher than that in the control group, respectively. There was a ninefold increase in mRNA expression of VEGF gene in tumor cells of ANB mice than that in control mice; however, there was no significant changes in ONB group. Expression of HIF gene was significantly lower in tumor cells of ONB and ANB group than in the control group. It is concluded that drinking ONB water has potential to inhibit tumor growth, however more preclinical and proof‐of‐concept studies are needed to confirm its safety and therapeutic effect.